Determinasi Pengungkapan Kepatuhan Syariah Pada Negara Gulf Cooperation Council (GCC) Berdasarkan Standar AAOIFI - Fauza Dwi Annisa Sabani; Mursyid Mursyid; Maisyarah Rahmi (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
Sharia compliance is a concept referring to adherence or conformity to the principles of Islamic law in various aspects of life, including economics, finance, business, and social matters. This research aims to analyze the factors suspected to influence Sharia compliance based on AAOIFI standards, namely Sharia supervisory boards and risk management. The study adopts a quantitative approach with data sourced from the financial reports of seven companies located in GCC countries. The method employed in this research is multiple linear regression analysis using SPSS version 25 software. The findings indicate that, partially, the educational background of Sharia supervisory board members, the number of Sharia supervisory board members, and liquidity risk have a positive impact on Sharia compliance. Conversely, the educational background in fiqh muamalah (Islamic commercial jurisprudence) of Sharia supervisory board members and credit risk have a negative impact on Sharia compliance.